Optimization of process parameter of sintered powder metallurgical TiC reinforced tungsten matrix composites. (December 2021) - Sukumar, S.; Saravanan, S.; Prabhu, T. Ram; Parameswaran, P.
Abstract : The W-TiC composites with various concentrations of TiC were produced via powder metallurgy. The high energy ball mill was used for the manufacturing of the samples. In this paper, we have selected (Taguchi Analysis) the optimizing parameters such as sintering temperature, and compaction pressure as inputs and corresponding outputs are compressive strength and microstructure. The compressive strength was analyzed by changing the three variances which found that, the compressive strength improved with the addition of TiC. The surface morphology of the sample was verified with SEM examination which confirms the improvement in the strength of material having higher concentration of TiC with higher sintering temperature and compaction pressure.